The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
PsycEXTRA Dataset 2009
DOI: 10.1037/e601852011-001
|View full text |Cite
|
Sign up to set email alerts
|

Early School Transitions and the Social Behavior of Children with Disabilities: Selected Findings From the Pre-Elementary Education Longitudinal Study

Abstract: Research (NCSER) supports a comprehensive research program to promote the highest quality and rigor in research on special education and related services, and to address the full range of issues facing children with disabilities, parents of children with disabilities, school personnel, and others.We strive to make our products available in a variety of formats and in language that is appropriate to a variety of audiences. You, as our customer, are the best judge of our success in communicating information effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 27 publications
1
32
1
Order By: Relevance
“…Children of families that participate in recreational and cultural activities are more likely to be involved in these activities [24,25,48]. Parental perceptions of neighborhood safety were related to the amount of community participation by their children with special education needs [45]. Parents of children with physical disabilities have reported that their overprotectiveness might limit their children's independent participation [14].…”
Section: Family-related Attributesmentioning
confidence: 98%
See 1 more Smart Citation
“…Children of families that participate in recreational and cultural activities are more likely to be involved in these activities [24,25,48]. Parental perceptions of neighborhood safety were related to the amount of community participation by their children with special education needs [45]. Parents of children with physical disabilities have reported that their overprotectiveness might limit their children's independent participation [14].…”
Section: Family-related Attributesmentioning
confidence: 98%
“…Higher family income, married status of parents and higher parental educational levels are related to higher participation and socialization of children with physical disabilities [37,44,45]. Family ecology, including family functioning, expectations, supports and resources are important considerations when planning services for young children with CP and their families [46].…”
Section: Family-related Attributesmentioning
confidence: 98%
“…Second, although research has been conducted on this subject for preschool and early elementary students, no studies focused on kindergarten, which is when many children begin their formal schooling and a significant developmental period for peer-related social competence for young children with disabilities. To illustrate the significance, researchers using the Pre-Elementary Education Longitudinal Study (PEELS) nationally representative data set found that children with disabilities with fewer or far fewer friends than their peers were significantly more likely to experience somewhat hard or very hard transitions into kindergarten (Carlson et al, 2009). Furthermore, researchers using the same data set found that limited social skills and difficulties with peer interactions in early school years predicted later peer victimization of children with disabilities (Son et al, 2014).…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…Forty percent of teachers who worked in very large districts used six or more strategies to facilitate transitions, compared with 58% of teachers who worked in medium districts. Thirty-two percent of teachers who worked in very low wealth districts used six or more strategies compared with 52% of teachers who worked in high wealth districts (Carlson et al, 2009).…”
Section: Illustrative Findingsmentioning
confidence: 99%
“…There were some statistically significant differences based on parent report, however. For example, parents of Hispanic children were more likely than parents of Black children or White children to report a somewhat hard or very hard transition to kindergarten (26%, 16%, and 13%, respectively) (Carlson et al, 2009).…”
Section: Illustrative Findingsmentioning
confidence: 99%